The Effect of Implementing the E-Filing System on Individual Taxpayer Compliance at the Bandung Medium Tax Office with Information Technology Knowledge as a Moderating Variable - Yuniawati, Ayi Srie; Azhari, Ceriska; Kartika, Tita (LPPM Universitas Sebelas April, 2025)
The deliberate and voluntary actions taken by taxpayers to satisfy their tax duties and exercise their rights, demonstrating a favourable attitude towards tax responsibilities, are referred to as tax compliance. This study uses information technology expertise as a moderating variable at the Bandung Intermediate Tax Office (KPP) to investigate how the installation of the e-filing system affects taxpayer compliance. Convenience sampling was used in the study, and 79 respondents' information was gathered using online surveys. Multiple linear regression analysis, moderation regression analysis, and path analysis approaches were applied in a quantitative manner.The results show that when information technology expertise is taken into account, the adoption of the e-filing system has no discernible impact on taxpayer compliance. The findings of the moderated regression analysis show that the association between the adoption of an e- filing system and taxpayer compliance is not moderated by information technology knowledge, as evidenced by the significant value of 0.845, which is higher than the cutoff point of 0.05